The dynamics of informal care provision in the Australian household panel survey: Previous work characteristics and future care provision - Nguyen, Ha Trong; Connelly, Luke (My University, 2017)
This study contributes to a small literature on the dynamics of informal care by examining the informal care provision choices of working‐age Australians. We focus on the impact of previous work characteristics (including work security and flexibility) on subsequent care provision decisions and distinguish between care that is provided to people who cohabit and people who reside elsewhere, as well as between the provision of care as the primary caregiver and provision in a secondary caring role. Our dynamic framework of informal care provision accounts for state dependence, unobserved heterogeneity and initial conditions. For both males and females, we find the existence of positive state dependence in all care states in both the short and medium term. Furthermore, the inertia in care provision appears to be stronger for more intensive care. We also find previous employment status has a significant deterrent effect on current care provision decisions. The effects on employment, however, differ according to the type of previous work, the type of care currently provided, and the gender of the caregiver. We also find that workers with perceptions of greater job security are nevertheless less likely to provide subsequent care. Our results suggest that workers’ perceptions about work flexibility and their stated overall satisfaction with work actually have no impact on their subsequent decisions to provide care in any capacity.
Economic Record
Keywords: Employment -- Labour force supply; Child Care; Labour market; Child Care; Employment; Labour force supply; Employment and unemployment